Resource Allocation in Paddy Farming Under Different Tenure Categories in Two Villages in East Java Indonesia - Mustadjab, Mochamad Muslich (1983)
The present study provides empirical evidence on resource allocation in paddy farming under different tenure categories based on data collected from 105 paddy farms by The Agro-Economic Survey of Indonesia (SAE), for the 1980/ 1981 wet season at two villages in East Java. To observe resource allocation in different tenure categories, Cobb-Douglas production function analysis was employed by introducing dummy variables for owner operator, fixed rental and mixed tenant. In this analysis the assumption that no difference exists in the slope of production function between share tenant and the other three tenure categories A dummy variable for village was also introduced to differences in production functions between the two being studied. The difference between pure owner tenant in terms of their constant terms or parameter and output elasticity of input or slope of the production function was also observed in this analysis . Analysis of resource use efficiency was done by using the ratio of Marginal value product (MVP) to its marginal factor cost to examine the allocation of the resources in paddy farming under different tenure categories. Results obtained from Least Square estimates based on the Cobb-Douglas type production function indicated significant differences between share tenant farms in their production function. Share tenant appeared to be in the lowest category in their paddy production, while the highest was mixed tenant followed by owner operator and fixed rental farms. Between pure owner and pure tenant there were significant differences in their constant term and their slopes of production function with respect to land and human labour input. This implied that there were significant differences in their land and human labour productivity. Pure owner appeared to be more productive in using their land input relative to pure tenant, and tenant appears more productive in using their human labour input than pure owner. Paddy farm income of share tenant was observed to be the lowest relative to the other tenure categories (significant at 1%). The average annual per capita income also appeared to be the lowest as compared to owner operator or fixed rental farmer, although statistically was not significant. Analysis of resource use efficiency indicated that for all categories of tenure input factors allocated. This implied that re-al1ocation were inefficiently of resources would have important impact on the yield of paddy. In this analysis, it was observed that hired human labour and current inputs, which consist of expenses on seed, insecticide, fertilizer and the rent of sprayer, were used below optimum levels